Assessing Advanced Propulsion Systems Using the Impact Monitor Framework - Utkarsh Gupta; Atif Riaz; Felix Brenner; Thierry Lefebvre; Patrick Ratei; Marko Alder; Prajwal Shiva Prakasha; Lukas Weber; Jordi Pons-Prats; Dionysios Markatos (Engineering Proceedings)
Presented in this paper is the Impact Monitor framework and interactive Dashboard Application (DA) validated through a use case, focusing on investigating the viability and competitiveness of future propulsion architectures for next-generation aircraft concepts. This paper presents a novel collaborative framework for integrated aircraft-level assessments, focusing on secure, remote workflows that protect intellectual property (IP) while enabling comprehensive and automated analyses. The research addresses a key gap in the aerospace domain: the seamless matching and sizing of aircraft engines within an automated workflow that integrates multiple tools and facilitates real-time data exchanges. Specifically, thrust requirements are iteratively shared between aircraft and engine modeling environments for synchronized sizing. Subsequently, the fully defined aircraft data are transferred to other tools for trajectory analysis and emissions and other assessments. The Impact Monitor framework and Dashboard Application demonstrate improved efficiency and data security, promoting effective collaboration across institutions and industry partners.